Структура Те-CdTe со свойством электронного переключения с памятью - Baidullaeva, А.; Borshch, V. V.; Veleschuk, V. P.; Vlasenko, O. I.; Dauletmuratov, B. K.; Levytskyi, S. N.; Mozol', P. E. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The formation of a tellurium film on the surface of a CdTe crystal under ruby laser pulse irradiation has been investigated. A method for fabricating a Te–CdTe structure with electronic switching and memory properties is also presented.